A new landhopper species of Myanmarorchestia (Crustacea: Amphipoda: Talitridae) from Yunnan, China. Issue 17 (11th May 2018) - Nakano, Takafumi; Tomikawa, Ko; Hou, Zhonge; Morino, Hiroshi
ABSTRACT: A new landhopper talitrid, Myanmarorchestia nunomurai Nakano and Morino, sp. nov., from Yunnan Province, China is described. Since species of Myanmarorchestia were known only from Mt. Victoria of the Arakan Mountains of Myanmar, this is the first record of the genus from China. Myanmarorchestia nunomurai is characterised by its coxal gills on gnathopod 2 to pereopod 6 without filamentous projections while the other congeners from Myanmar possess some/all of the coxal gills with filamentous projections. Additionally, M. nunomurai can be diagnosed by the sexually dimorphic uropod 2, of which the outer ramus bears a robust seta on the midlateral surface and a few rows of small teeth on the middle to distodorsal surface. http://zoobank.org/urn:lsid:zoobank.org:pub:3C014FFC-F4D6-4F18-8188-33672367ABB1